Analysis of Pedagogical Content Knowledge (PCK) Levels of Teachers at SMP Negeri 21 Ambon - Asrul, Asrul; Lasaiba, Mohammad Amin (JENDELA PENGETAHUAN, 2022)
A teacher can be said to be professional and not only can master the material and concepts but must master how to teach and how learning strategies can be conveyed to students properly. These two things are between material (content) and how to teach (pedagogy), which are mutually sustainable and cannot be separated. The importance of continuity between material and pedagogics emerges, and a new understanding of how to combine material knowledge and convey it to students, namely pedagogical content knowledge (PCK), appears. The essential components of PCK are Pedagogical Knowledge (PK) and Content Knowledge (CK). This type of research is descriptive research. Descriptive research. Quantitative analysis through categorization. This study uses quantitative research as the process of data collection and processing. Quantitative research is research that uses a lot of numbers, from collecting data and interpreting data to presenting results. Based on the calculation of the PCK level at SMP Negeri 21 Ambon through the teacher's PCK test consisting of 52 open-ended questions, it is known that the ideal means is 26, and the perfect standard deviation is 7.78. Furthermore, it was found that 3 teachers were in the high PCK category, 2 teachers were in the medium PCK category, and 1 teacher was in the low PCK category.